Problemas emocionais e comportamentais e uso de serviços educacionais e de saúde em escolares - Seraceni, Mayra Fernanda Ferreira (2013)
Schools are appropriate contexts for the investigation of mental health, emotional and behavioral problems in children and adolescents. In Brazil there are few studies that compare behavioral problems in students of mainstraim public and private schools associated with the use of educational and mental health facilities. The present study had the objective of investigating emotional and behavioral problems, as well as its associated risk and protection factors, in Elementary Schools students from private and public mainstream schools. A cross-sectional study was made and based on the proposed objectives the sample attended convenience criteria. The sample was composed of 357 students, age range 6 to 12 years old, from public and private schools and their respective parents (176 are students from three public schools in Barueri and 181 students from one private school in Sao Paulo downtown). Data collection instruments were: a) questionnaire with social-demographic data and information on the use of health services; b) Child Behavior Checklist for ages 6 to 18 (CBCL/6-18); c) recording of academic performance through the identification of annual average grades in Portuguese and Mathematics. Descriptive analysis were carried out through the use of simple frequency tables and crossed tables; analyses of variance for the comparison of average scores in CBCL/6-18 between groups; correlation analysis for the verification of possible associations among variables of sample characterization with scores of emotional and behavioral problems, social and academic competences indicators, as well as indicators of social-demographic characterization and use of educational and health services and a technique of logistic regression to determine the probability or result of a child to be classified as border-line/clinical in the scales of externalizing, internalizing or total behavioral problems on CBCL/6-18 based on predictive factors: gender, age, school (public or private), caretaker s age, socioeconomic classification, average grade in Mathematics and Portuguese and scores in the scales of competences for performing activities, socialization and academic performance on CBCL/6-18. The main results indicate emotional and behavioral problems in both groups. Observa-se de modo geral que os pais cuidadores de crianças das escolas públicas perceberam um maior número de problemas de comportamento em seus filhos quando comparados aos informantes da escola particular. It was observed that parents of children enrolled in public schools perceive a greater number of behavioral problems in their children compared to parents of children enrolled in private schools. In terms of academic variables, both groups achieved similar results in average grade in Portuguese and Mathematics and academic performance assessed by CBCL/6-18, what indicates that participants do not present problems in this area. It was observed that according to parental perception concerning the existence internalizing behavioral problems (Private=38,10%; Public=30,70%) was greater if compared to externalizing (Private=15,50%; Public=15,30%). Data show that children that do not present emotional and behavioral difficulties according to the caretaker s report use more psychological services compared to the group that present borderline/clinic scores in the total scale of emotional and behavioral problems of CBCL/6-18. In both groups logistic regression model has allowed the verification of concomitant associations among academic and social competences and the caretaker s age with the result of emotional and behavioral problems of children. We concluded that the identification of these concomitant association enhance the need of mental health strategies focused on the promotion of social abilities and monitoring and management of academic difficulties of these children. Thus, such actions can be developed in the school locus though workshops and lectures with orientations on the management of emotional and behavioral problems or intervention strategies and necessary follow-up.